Study of Drug Utilization on Acute Poisoning Cases Treated at Tertiary Care Hospital - Todi, Dr. Sreya (International Journal of Innovative Research in Medical Science, 2018)
Acute poisoning is common everywhere in medical emergency. Acute poisoning may be due to deliberate exposure to drugs, chemicals and natural toxins or accidental which is emergency for common medical health. The main aim of this study was to investigate the pattern of drug utilization, poisoning agents, and outcome in patients with treated acute poisoning. Material and Methods: This prospective cross sectional study was carried out in the emergency department of a tertiary care centre over a one year period. Result: During the period of 1 year total 310 Acute poisoning cases were recorded by us. Out of 310 acute poisoning cases 170(54.8%) were male where as females were 140(45.2%). The majority of cases were from age group of 20 -50 years in males whereas mean age of female patients was 37.3 years and majority of the cases were from 25-50 age group. The most common route of exposure to poisons (69.6%) was ingestion and followed by dermal exposure (in cases of venomous animal exposures) (25.8%) and inhalation (4.6%).The most common symptomatic treatments given to the patients were antimicrobials (88.7% of cases), antiemetics (82.6%% of cases), H2 blockers (72.9% of cases) and Atropine (51% of cases), pralidoxime (41.6% of cases) Proton pump inhibitors and Vasopressor agents etc respectively. The most commonly prescribed specific antidotes were Anti-snake venom (ASV) (12.9% of cases).Conclusion: In the present study, the main causes of poisoning were identified as household products in urban areas of India. Awareness about the dangers of such poisons should be the added responsibility of health and hospital authorities. Poison control center establishment in the region will also help in preventing and controlling such poisoning events.